IMPROVING STUDENTS’ LISTENING COMPREHENSION THROUGH ENGLISH SONG IN SECOND GRADE OF MTS CIJAWURA BANDUNG - Wahyu Satya Gumelar; Nida Aisya Suryadi; Diah Khadijah (Media Nusantara, 2018)
The research entitled improving students’ listening comprehension throughEnglish song in second grade of MTS Cijawura. The aim of this researchpaper is to investigate the improvement of students’ listening comprehensionthrough English song as a part of the learning process in the classroom. Thisresearch was an action research consisting of three cycles. The participants of this research were 32 students of second grade at MTS Cijawura in the academicyear of 2016/2017. The data obtained were qualitative and quantitative. Thequalitative data were gained by observation sheet, interview, and questionare. The quantitative data were gained from the listening test that were conducted before the implementations and after the implementation in cycle I, cycle II, and cycle III. The actions implemented in each cycle were using English song that enable the students to improve their listening comprehension. The research findings from the test in first cycle until third cycle that by using of English song, students’ could improve their listening comprehension. The means score from 53 in pretest, 63.4 in cycle I, 77.7 in cycle II, 83.4 in cycle III. There were some good improvements in some aspects such as their new vocabulary and motivation to learn English  more. Futhermore most of students give positive responses toward the use of English song in teaching listening comprehension.